Enhanced thermal stability by introducing TiN diffusion barrier layer between W and SiC. Issue 9 (7th March 2019) - Cheng, Ping; DelaCruz, Steven; Tsai, Dung‐Sheng; Wang, Zhongtao; Carraro, Carlo; Maboudian, Roya
Abstract: The combination of W and SiC has many applications such as a hot cell of a thermionic energy converter, nuclear material, and high temperature microelectronics. In this study, a 2 µm thick TiN film is introduced as a diffusion barrier between SiC and W to avoid the inter‐diffusion reaction at high temperature. The effect of annealing temperature on the surface morphology and microstructure of the TiN film is studied to explore its high temperature stability. Then 500 nm W film is sputtered on the TiN film to characterize the inter‐diffusion and stability of the W/TiN/SiC multilayer at 1100°C by XRD, Raman spectroscopy and cross‐sectional EDS mapping techniques. The results indicate that the W/TiN/SiC multilayer is very stable even when heated at 1100°C for 25 hours.